2000
DOI: 10.1063/1.1326064
|View full text |Cite
|
Sign up to set email alerts
|

Transient resonance Raman spectroscopy and density functional theory investigation of iso-polyhalomethanes containing bromine and/or iodine atoms

Abstract: We report additional transient resonance Raman spectra and density functional theory computations for the products formed following ultraviolet photoexcitation of solution phase polyhalomethanes containing bromine and/or iodine atoms. We show that the iso-polyhalomethane photoproduct is responsible for the intense transient absorption band observed in the 350-470 nm region after ultraviolet excitation of polyhalomethanes in the solution phase. We examine the trends and correlation in the density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
103
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(115 citation statements)
references
References 111 publications
12
103
0
Order By: Relevance
“…4,5 Excitation at 193 nm favors C-Br cleavage ͑branching ratio of 3.5:1 C-Br:C-I͒. 5 The same trends are observed in solution phase experiments including steady state 6 and timeresolved resonance Raman [7][8][9] and femtosecond transient absorption at 266 nm. 10 Recent theoretical calculations provide additional insight into the dissociation of CH 2 BrI.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…4,5 Excitation at 193 nm favors C-Br cleavage ͑branching ratio of 3.5:1 C-Br:C-I͒. 5 The same trends are observed in solution phase experiments including steady state 6 and timeresolved resonance Raman [7][8][9] and femtosecond transient absorption at 266 nm. 10 Recent theoretical calculations provide additional insight into the dissociation of CH 2 BrI.…”
supporting
confidence: 54%
“…9,12 The calculations of Liu et al 12 suggest that the iso-CH 2 I -Br compound has a strong absorption band at ϳ315 nm ͑f = 0.46͒. The second transition at ϳ445 nm ͑f = 0.003͒ is significantly weaker than the corresponding transition of iso-CH 2 Br-I.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter channel, where it has been found, is usually assumed to involve a constrained symmetric multicenter transition state, which has not been identified computationally. 2 The iso-halons are well-known condensed-phase reactive intermediates that possess a halogen−halogen bond; [3][4][5][6][7][8][9][10][11][12][13][14][15] yet, few studies have suggested a role for these species in the gas-phase chemistry of halons. In recent studies of the multiphoton dissociation of the halons CHX3 and CX4, (X = Br,I), Quandt and coworkers suggested on the basis of secondary evidence a mechanism that involved the isospecies.…”
mentioning
confidence: 99%